2010
DOI: 10.1111/j.1440-1835.2010.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Species richness of marine macrophytes is correlated to a wave exposure gradient

Abstract: Wave exposure is one of the fundamental variables of the coastal environment and many coastal processes are affected by waves and wave-induced water motion. Directly or indirectly, waves affect the lives of many coastal macroalgae and seagrasses. Although the idea that waves can affect macrophyte distribution and biodiversity is not new, it remains poorly examined. We looked at how a gradient of wave exposure, determined using the surf similarity number, influences the species richness of macrophytes among phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 61 publications
(134 reference statements)
1
26
0
Order By: Relevance
“…For example, Wing and Patterson (1993) found that higher wave motion decreased light intensity. Nishihara and Terada (2010) found that Phaeophyta increased in species richness with increasing wave exposure, which may explain the higher percentage of phaeophyta in the Jiahe River estuary and at Zhifu Island in April-June (Table 5).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Wing and Patterson (1993) found that higher wave motion decreased light intensity. Nishihara and Terada (2010) found that Phaeophyta increased in species richness with increasing wave exposure, which may explain the higher percentage of phaeophyta in the Jiahe River estuary and at Zhifu Island in April-June (Table 5).…”
Section: Discussionmentioning
confidence: 91%
“…Together with other environmental variables, wave exposure may affect macroalgal distribution (Gaylord et al, 2002;Nishihara and Terada, 2010). On the Yantai coast, the strongest waves are mainly in the northeast direction, and the tidal range is about 152 cm (Liu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al (2011) also noted that seasonal variations in macroalgal assemblages near the MLW are more dynamic than those in assemblages in the deeper subtidal or higher intertidal zones. In many studies of the effects of wave exposure on macroalgal communities, intermediate levels of water motion enhance diversity and abundance of seaweeds by accelerating nutrient and gas exchange (Prathep 2005, Nishihara andTerada 2010). In summary, our intensive study of macroalgal assemblages on the Marado coast provided great insights into the distribution pattern of macroalgal assemblages in unpolluted marine areas of Jeju Island.…”
Section: Resultsmentioning
confidence: 99%
“…2). Turf or mat-forming macroalgae can effectively defend themselves against wave action and desiccation stress by folding each other, simple forms, and tough and protractile thallus (Hay 1981, Prathep 2005, Nishihara and Terada 2010, Nishihara et al 2011. S. thunbergii, which constituted a large portion of the high and mid-intertidal assemblage, can effectively resist desiccation by retaining water among the numerous small leaves that surround its branches and by folding onto other individuals as well as being protected from wave action by its tough branches and cylindrical outline.…”
mentioning
confidence: 99%
“…wave action). Indeed, wave exposure is one of the major factors directly or indirectly influencing the structure of algal assemblages (Rindi and Guiry 2004, Nishihara and Terada 2010, Borja et al 2013. Although increasing wave action is a key factor in supplying nutrients for macroalgae (Martins et al 2013), hydrodynamic pressure can also remove epibionts and prevent them from settling (Kersen et al 2011).…”
Section: Discussionmentioning
confidence: 99%